(untitled) (Journal of Plant Disease Sciences, 2019)
Carrot (Dacus carota var. sativus.) is a top-ten economically important vegetable crop in the worldfor its tuber production. However, its production is hindered by both abiotic and biotic factors. Among the biotic factors,the root knot nematodes is the most widely devastating pests that inflicting direct and indirect damage to carrot, especially in resource poor farmers. The root knot nematode damage causes an increase in carrot yield prices and even limits produce availability. Therefore, this paper review has been emphasized on the different practiced root knot nematode managements. Several management methods existed to suppress root knot nematodes and reduce their damage in carrot crop includescultural practices, biological, host resistance crops, chemicals, physical and integrated root knot managements were included. It was also indicated some future directions to be implemented. It is hoped that this article would provide good inspirational tools to users to create a sound scientific knowledge base for sustainable management of root knot nematodes in carrotcultivated area.